Pré-regulador com derivação central baseado na célula de comutação de três estados para aplicação em no-breaks - Câmara, Raphael Amaral da (2008)
This work presents the study of the center tapped preregulator based on three-state switching cell with power factor correction characteristics for applications in universal input and output voltages UPS. The main features of the proposed converter are: reduced conduction and commutation losses on the controlled switches by the fact that they do not conduce directly the input current to the output but sharing this current with magnetic components; magnetic components operating with the double of switching frequency reducing weight and volume; reduced high-frequency current ripple on the output filter, reduced capacitors value; connection between input power supply and converter output enabling the use of UPS inverter and by-pass. Theoretical analysis, design procedure, simulation and experimental results from a 3kW laboratory prototype are presented in order to validate the principle of operation of the proposed system.